Supporting Real Time Decision-Making The Role of Context in Decision Support on the Move - Burstein, Frada; Brezillon, Patrick; Zaslavsky, Arkady; SpringerLink (Boston, MA Springer US Imprint: Springer, 2011)
Introductory Note Frada Burstein, Patrick Brézillon and Arkady Zaslavsky Theme I: Theories of Real-Time Decision Support Challenges of Real-Time Decision Support Daniel J. Power Improvisation of Model for Real-Time Decision Making Eric W. Stein Theme II: Tools and Technologies for Context-aware Real-Time Decision Support Context Prediction in Pervasive Computing Systems: Achievements and Challenges Andrey Boytsov and Arkady Zaslavsky A Contextual Menthodology for Modelling Real-Time Decision Making Support Patrick Brézillon Towards Real-Time Context Awareness for Mobile Users: A Declarative Meta-Programming Approach Seng W. Loke The Role of Context for Crisis Management Cycle Florence Aligne and Juliette Mattioli The Contextual and Collaborative Dimensions of Avatar in Real-Time Decision Making Norita Ahmad and Reza Barkhi Theme III: Case Studies Beyond Rationality: Information Design for Supporting Emergent Groups in Emergency Response Tung Bui and Ina Sebastian Dynamic Emergency Response Management for Large Scale Decision Making in Extreme Hazardous Events Murray Turoff, Connie White and Linda Plotnick Partially Distributed Emergency Teams: Considerations of Decision Support for Virtual Communities of Practice Linda Plotnick, Murray Turoff and Connie White Why Real-Time Transaction Processing Fails to Capture the Context Required for Decision Support Fergal Carton, Frederic Adam and Patrick Brézillon Continuous Auditing as a Foundation for Real Time Decision Support: Implementation Challenges and Successes Robert Baksa and Murray Turoff Towards a ?Just-in-Time? Distributed Decision Support System in Health Care Research Ziad Kobti, Anne W. Snowdon, Robert D. Kent, Gokul Bhandari, Shamual F. Rahaman, Paul D. Preney, Carol A. Kolga, Barbara Tiessen and Lichun Zhu Context Modelling in Time Critical decision Support for Medical Triage Shane Grigsby, Frada Burstein and Nyree Parker Efficient Context Prediction for Decision Making in Pervasive Health Care Environments: A Case Study Yves Vanrompay and Yolande Berbers On-demand Assistance in Handling Ammunition: Development of a Mobile Ammo DSS Supavich Pengnate, Ramesh Sharda, David Biros, Michael Hass and Upton Shimp Development of a Mobile Situation Awareness Tool Supporting Disaster Recovery of Business Operations Pedro Antunes, Claudio Sapateiro, Gustavo Zurita and Nelson Baloian
Challenges of Real-Time Decision Support -- Improvisation of Model for Real-Time Decision Making -- Context Prediction in Pervasive Computing Systems: Achievements and Challenges -- A Contextual Methodology for Modelling Real-Time Decision Making Support -- Towards Real-Time Context Awareness for Mobile Users: A Declarative Meta-Programming Approach -- The Role of Context for Crisis Management Cycle -- The Contextual and Collaborative Dimensions of Avatar in Real-Time Decision Making -- Beyond Rationality: Information Design for Supporting Emergent Groups in Emergency Response -- Dynamic Emergency Response Management for Large Scale Decision Making in Extreme Hazardous Events -- Partially Distributed Emergency Teams: Considerations of Decision Support for Virtual Communities of Practice -- Why Real-Time Transaction Processing Fails to Capture the Context Required for Decision Support -- Continuous Auditing as a Foundation for Real Time Decision Support: Implementation Challenges and Successes -- Towards a ?Just-in-Time? Distributed Decision Support System in Health Care Research -- Context Modelling in Time Critical decision Support for Medical Triage -- Efficient Context Prediction for Decision Making in Pervasive Health Care Environments: A Case Study -- On-demand Assistance in Handling Ammunition: Development of a Mobile Ammo DSS -- Development of a Mobile Situation Awareness Tool Supporting Disaster Recovery of Business Operations.
Keywords: Decision support systems; Real-time data processing; Electronic books